Synthesis,characterisation and biological activity studies of organo-bridged metal schiff base complexes with qinoxaline derivative - Mohlala, Reagan Lehlogonolo (University of Limpopo, 2016)
Imidazolyl-salicylaldemine Schiff base ligands were prepared by the condensation of different substituted salicylaldehydes with histamine dihydrochloride: 2,4-di-tert-butyl-6-{[2-(1H-imidazol-4-yl)-ethylimino]-methyl}-phenol L1; 4-methoxy-6-{[2-(1H-imidazol-4-yl)-ethylimino]-methyl}-phenol L2; 2-ethoxy-6-{[2-(1H-imidazol-4-yl)-ethylimino]-methyl]-phenol L3; 2-methyl-6-{[2-(1H-imidazol-4-yl)-ethylimino]-methyl}-phenol L4; 3-methyl-6-{[2-(1H-imidazol-4-yl)-ethylimino]-methyl}-phenol L5; 4-methyl-6-{[2-(1H-imidazol-4-yl)-ethylimino]-methyl}-phenol L6; 5-methyl-6-{[2-(1H-imidazol-4-yl)-ethylimino]-methyl}-phenol L7; 2-tert-butyl-6-{[2-(1H-imidazol-4-yl)-ethylimino]-methyl}-phenol L8; 3-methoxy-6-{[2-(1H-imidazol-4-yl)-ethylimino]-methyl}-phenol L9; 4-tert-butyl-6-{[2-(1H-imidazol-4-yl)-ethylimino]-methyl}-phenol L10. The ligands were characterised by 1H, 13C and 15N NMR, FT-IR, UV-vis spectroscopic methods, mass spectroscopy and elemental analysis where possible. Reactions of L1-L9 with MnCl2 and CuCl2 yielded complexes C1–C18 all in a ratio of (1:1). C1 – C18 here, i.e. C18 2-methyl-6-{[2-(1H-imidazol-4-yl)-ethylimino]-methyl}-phenol Cu(II) chloride. The complexes that are paramagnetic were mainly characterised by FT-IR spectroscopy, UV-vis spectroscopy, mass spectroscopy and elemental analysis. Reaction of L9 with ZnCl2 yielded 2-methyl-6-{[2-(1H-imidazol-4-yl)-ethylimino]-methyl}-phenol Zn(II) chloride, C19 which is diamagnetic and was characterised by 1H, 13C NMR spectroscopy Mass spectroscopy and Elemental analysis. Condensation of o-phenylenediamine and glyoxylic acid yielded 2-quinoxalinone Q1, reaction of 2-quinoxalinone and benzenesulfonyl chloride yielded 2-benzenesulfonyloxyquinoxaline Q2, and the reaction of 2-benzenesulfonyloxyquinoxaline with ethynyltrimethylsilane yielded 2-ethynyltrimethylsilanequinoxaline Q3. Quinoxaline and its preceding starting compounds were characterised by 1H, 13C NMR spectroscopy. Attempts to cross couple Schiff base complex C19 and Q3 via Sonogashira cross coupling mechanism method was not successful after two attempts from following two different reaction routes and conditions. The trans-metalation route yielded quinoxaline derivative QA in good yield after the reaction of Q3 with ZnCl2 and, C19 in the presence of Et2NH which were characterised by NMR (1H, 13C and HMBC), Mass spectroscopy (HRMS) and Elemental analysis. iv These reactions showed hydroamination instead of coordination in yield of (90%) using ZnCl2 as catalyst and 60% using C19 as catalyst. Biological activity studies were done by quantitative antibacterial activity by assay of minimum inhibition concentration (MIC). Bacterial cells used as pathogenic microorganisms were gram negative: Escherichia coli and Pseudomonas aeruginosa, gram positive: Staphylococcus aureus and Enterococcus faecalis. Compound used for testing : L9, C19, C18, C9, Q3 and QA. All compounds were found to be active against bacterial cells of E. coli and E. faecalis with a minimum inhibition concentration of 0.004 mg/ml average and total activity of 500 mg/ml average. For all compounds used for testing bacterial activity against cells of P. aeruginosa and S. aureus, the lowest concentration was 0.063 mg/ml average and total activity of 266 mg/ml average for C18. P. aeruginosa and S. aureus were found to be less active compared to bioactive standards used for E. coli and E. faecalis.
Thesis (M.Sc.(Chemistry)) -- University of Limpopo, 2016
Keywords: Imidazolyl-salicylaldemine Schiff; Chemistry; Copper -- Structure-activity relationships